THE DIFFERENCE CHARACTERISTIC OF RELATIONSHIP BETWEEN SARCOPENIA AND BLOOD PRESSURE ACCORDING TO GENDER IN KOREAN POPULATION. (June 2018) - Kim, J.K.; Lee, T.S.
Abstract : Objective: : High blood pressure (BP) has been known to the risk factor of cardiovascular disease (CVD). However, the extremely lower BP is also known to the risk factor of CVD. The sarcopenia has been highlighted in older people because lower muscle mass is associated the frailty and chronic disease. The present study aimed to uncover the association between the sarcopenia and BP in Korean population Design and method: This study collected data from 5, 045 participants (60 or more age) in the Korea National Health and Nutrition Examination Surveys (2008 – 2011). The sarcopenia was defined as lower appendicular skeletal muscle (ASM) adjusted by weight (Men < 29.5%, Women < 23.2%). Results: : The prevalence of sarcopenia as estimated by ASM adjusted by weight was 26.4% in men and 28.7 in women. The ratio of hypertension was 42.7% in men and 49.3% in women. We classified all population into 8 groups according to systolic and diastolic BP. The covariates included age, dyslipidemia medication, current smoke, regular exercise, alcohol consumption, fasting glucose. After adjusted these all covariates, the adjusted OR of the lowest systolic BP (SBP), the second lowest SBP, and the highest SBP groups were 1, 2.39, and 19.45 in men, and 1, 0.35, and 2.05 in women. The adjusted OR of the lowest diastolic BP (DBP), the second lowest DBP, and the highest DBP groups were 1, 1.10, and 1.43 in men, and 1, 0.70, and 1.149 in women. Collectively, the association between sarcopenia and blood pressure showed J-curve shape in Korean women. Conclusions: : The relationship between sarcopenia and blood pressure was different according to gender in Korean population.